Substrate integrated waveguide based cavity‐backed self‐triplexing slot antenna for X‐Ku band applications. Issue 4 (27th January 2020) - Nigam, Padmini; Agarwal, Rahul; Muduli, Arjuna; Sharma, Sandeep; Pal, Amrindra
Abstract: A planar substrate integrated waveguide (SIW) based cavity‐backed self‐triplexing slot antenna is proposed for X‐Ku band applications. The antenna comprises of the SIW cavity, radiating slots, and feeding networks. The radiating slots; that are etched on the upper metallic plane of the SIW, are backed up by the three radiated quarter cavities (QCs). The radiating slots in the respective QCs are of different lengths, excited by three separated orthogonal feed lines to resonate at three different frequencies as 11.01, 12.15, and 13.1 GHz. By fine‐tuning the antenna parameters, an intrinsic input port isolation of better than 26 dB is realized which helps in achieving the self‐triplexing property. The behaviors of individual cavity modes at three resonant frequencies are explained with the help of Z‐parameter. The proposed antenna layout is easy to integrate with the planar circuit. The proposed antenna is fabricated and measured results display a close concern with the simulated results. Moreover, a unidirectional radiation pattern and gain of 5.1, 5.54, and 6.12 dBi at resonant frequencies are realized.